Methodology of Organizing Musical Gymnastics in High Schools - Kazakov Shavkat Norqobilovich (International Journal on Integrated Education, 2023)
This article analyzes the specific aspects of musical rhythmic gymnastics, the requirements for the organization of lessons related to this sport, recommendations on the methodical support of lessons, and the compatibility of this sport with the age and physiological characteristics of secondary school students.